Use of computer databases in a specialized aquatic information service - Maclean, J. L. (1993)
Database may hold the future but not the present; the gap in their coverage are still too big. The old-fashioned bibliography still has a long life. Online facilities are by no means available to everyone and in any case most databases store data only from the last 10-12 years. A printed bibliography can and does form a base from which to start looking for information. Researchers should always treat a database printout with caution, remember WYSIWYG. What you see is what you get.
Keywords: Online facilities -- Fisheries and Aquatic Resources